Interlayer shear coupling in bilayer graphene - Jinglan Liu; Chunhua Zhu; Zilong Zhang; Qiancheng Ren; Xuewei Zhang; Yang Zhang; Yanhan Jin; Wei Qiu; Hongtao Wang; Junhua Zhao; Pei Zhao (npj 2D Materials and Applications, 2022)
Abstract The interfacial shear coupling (ISC) governs the relative in-plane deformations of layered two-dimensional (2D) van der Waals (vdW) materials, which is significant for both the fundamental theory of solid mechanics and the stability design of 2D devices. Here we study the representative ISC of 2D vdW stacks using bilayer graphene (BLG) and isotope-labeled Raman spectroscopy. The results show that under uniaxial tensile strain, the ISC between two graphene layers evolves sequentially with bonding, sliding and debonding process, and the corresponding interfacial shear strength is inversely proportional to the sample size. Molecular dynamics (MD) simulations demonstrate the origin of this inverse proportionality as stronger interlayer vdW interaction induced by the edge lattices and atoms of BLG that have more degrees of freedom. These results not only provide new fundamental insights into the multiscale interpretation of macroscopic interfacial shear properties of 2D vdW stacks but also have great potential in guiding the design of graphene-based composite materials and flexible 2D electronics.